2005
DOI: 10.1016/j.cub.2005.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Anatomical, and Functional Organization of the Drosophila Olfactory System

Abstract: These Or expression and ORN connectivity maps provide further insight into the molecular, anatomical, and functional organization of the Drosophila olfactory system. Our maps also provide an essential resource for investigating how internal odor representations are generated and how they are further processed and transmitted to higher brain centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
1,271
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 887 publications
(1,339 citation statements)
references
References 68 publications
46
1,271
1
4
Order By: Relevance
“…Specifically, Gr-Gal4 drivers were combined with GFP reporters that localize to axons and synapses, such as syn-GFP or CD8-GFP, followed by analysis of whole brain preparations using confocal microscopy. These studies have revealed that, unlike in the fly olfactory system, where precise axonal projections of OSNs to specific antennal lobe glomeruli are the rule [102,103], taste neurons send their axons to loosely defined, widely circumscribed zones in the SOG or thoracic ganglia [36,42]. For example, labial palp GRNs that express Gr5a project to large areas in the lateral and anterior region of the SOG, whereas the Gr66a-expressing GRNs project to the medial part of the SOG (Fig.…”
Section: Signal Transductionmentioning
confidence: 99%
“…Specifically, Gr-Gal4 drivers were combined with GFP reporters that localize to axons and synapses, such as syn-GFP or CD8-GFP, followed by analysis of whole brain preparations using confocal microscopy. These studies have revealed that, unlike in the fly olfactory system, where precise axonal projections of OSNs to specific antennal lobe glomeruli are the rule [102,103], taste neurons send their axons to loosely defined, widely circumscribed zones in the SOG or thoracic ganglia [36,42]. For example, labial palp GRNs that express Gr5a project to large areas in the lateral and anterior region of the SOG, whereas the Gr66a-expressing GRNs project to the medial part of the SOG (Fig.…”
Section: Signal Transductionmentioning
confidence: 99%
“…Molecular, genetic, and neurosensory knowledge in D. melanogaster frames the most complete picture of an olfactory system that is available, from odorant receptor genes to neuroanatomy and central processing of the olfactory input (Couto et al 2005;Benton et al 2007;Jefferis et al 2007;Dickson 2008). A current challenge is to further expand our view to also include odor-mediated behavior that reflects the entire integration pathway from ligand-binding to motor output.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of the Drosophila olfactory system has advanced rapidly, including the anatomy of primary sensory sensilla, their functional roles, and molecular identification of many olfactory receptors (Stensmyr et al, 2003;Couto et al, 2005;Laissue and Vosshall, 2008). However, the integration of primary sensory information is not well understood (Dobritsa et al, 2003;Couto et al, 2005; and will probably require detailed descriptions of individual sensory neuron responses to fluctuating concentrations of odorant chemicals, including their polarities and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the integration of primary sensory information is not well understood (Dobritsa et al, 2003;Couto et al, 2005; and will probably require detailed descriptions of individual sensory neuron responses to fluctuating concentrations of odorant chemicals, including their polarities and dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation